(untitled) (Baghdad Science Journal, 2019)
The organation ⁄monomer N-naphthylacrylamide (NAA) was prepared; subsequently the synthesized monomer was successfully copolymerized with acrylicacid (AA) and methylacrylate (MA) by free radical technique using dry benzene as solvent and benzoyl peroxide (BPO) as initiator. The overall conversion was kept low (≤ 10% wt/wt) for all studies copolymers samples. The synthesized monomer and copolymers were characterized using Fourier transform infrared spectroscopy (FT-IR), and their thermal properties were studied by DSC and TGA. The copolymers compositions were determined by elemental analysis. Kelen-Tudes and Finmman-Ross graphical procedures were employed to determine the monomers reactivity ratios. The derived reactivity ratios (r1, r2) are: (0.048, 0.687) for (NAA-co-AA) and (0.066, 0.346) for (NAA-co-MA). Based on the average reactivity ratios, sequence distribution of monomers in the copolymers and the microstructure of copolymers were calculated by statistical method and found that these values are in agreement with the derived reactivity ratios.